Temperature-dependent cyclic plastic deformation of U75VG rail steel: Experiments and simulations. (October 2022) - Kan, Qianhua; Zhao, Jizhong; Xu, Xiang; Wang, Ziyi; Zhang, Xu; Wang, Ping
Highlights: The temperature-dependent cyclic feature and ratcheting behavior of U75VG rail steel are investigated. A temperature-dependent visco-plastic constitutive model is established. The dynamic strain aging effect is considered in the proposed model. The full implicit integration algorithm is derived, and the finite element implementation is performed. The temperature-dependent cyclic feature and ratcheting behavior are simulated. Abstract: To reveal the temperature-dependent cyclic plastic deformation of U75VG steel, the monotonic tension, strain- and stress-controlled cyclic deformation experiments are carried out at different temperatures. The results show that the U75VG rail steel shows the cyclic softening, cyclic hardening and cyclic softening at 278 K, 573 K and 873 K. Moreover, the U75VG rail steel exhibits obvious ratcheting behavior at differ-ent temperatures, and the ratcheting strain depends on the applied mean stress and stress amplitude. The ratcheting strain is restrained at 573 K due to the influence of dynamic strain aging, while it rapidly increases at 873 K due to increasing the viscos-ity at high temperatures. A temperature-dependent cyclic plastic model is constructed to consider the influence of dynamic strain aging on the cyclic plastic deformation. By comparing the simulation and experimental results, the prediction ability of the proposed model for U75VG rail steel under different temperatures is verified.